Community Antibiotic Consumption in Cyprus for the Period 2015 to 2022 - Eirini Mitsoura; Ioannis Kopsidas; Pambos Charalambous; Georgios Papazisis; Nikolaos Raikos; Zoi Dorothea Pana (MDPI AG, 2024)
Background: Cyprus currently reports to ESAC-Net the total consumption of antimicrobials, without distinguishing between hospital and community-based antibiotic use. As a result, these data can only provide generalized insights into antimicrobial trends in the country. Aim: This study is a first attempt to retrospectively analyze community antibiotic consumption in Cyprus for the period of 2015 to 2022. Material and Methods: Data on community antimicrobial consumption between 2015 and 2022 were extracted from Pharmatrack's database. Orally administered dispensed antibiotics were categorized under the J01 group of the WHO Anatomical Therapeutic Chemical (ATC) classification and by the WHO's AWaRe classification of antibiotics. Antibiotic consumption was calculated in both packages consumed and per 1000 inhabitants, overall, by year of consumption and districts. Results: During the period of 2015-2022, there was variability in the mean outpatient antibiotic consumption per 1000 inhabitants among the five districts in Cyprus. Community consumption increased by 38% throughout the study period. Additionally, a decrease of 3% in the consumption of WHO 'Access' antibiotics was observed, accompanied with a concurrent increase of 3% in the 'Watch' group. Specifically, in 2022 the WHO 'Access' group consumption in the Cypriot community was 48%, significantly lower than the WHO's goal of 60% and the EU's goal of 70% for 'Access' antibiotic consumption. Conclusions: Antibiotic consumption in the community of Cyprus between 2015 and 2022 demonstrated substantial variability among districts, with higher consumption in less populated areas. There was an increasing trend in community consumption over the years and a decreasing trend in the percentage of 'Access' antibiotics prescribed.